“My First Year in The University”: Students’ Expectations, Perceptions and Experiences - Lee, Kam-Fong; Ang, Chin-Siang; Dipolog-Ubanan, Genevieve (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
This study aimed to explore students’ first year experience to provide insights that may prove to be useful for institutional policy and practice. A semi-structured interview was conducted on 30 undergraduates from a private university to examine their perceptions, experiences, and attitudes towards first year experience. Themes were derived from the analysis of the transcribed interview transcripts. The results showed that in general students pursue tertiary education as it can guarantee their career prospect and intellectual development. Moreover, classroom engagement and academic staff engagement on students were less crucial in comparison to peer engagement. However, the students’ perceptions of studentship and quality of teaching were positive. Lastly, most students were satisfied with their first year experience in the university. Practical implications, recommendations and limitations for future practice are put forth